A Tumor‐Microenvironment‐Responsive Lanthanide–Cyanine FRET Sensor for NIR‐II Luminescence‐Lifetime In Situ Imaging of Hepatocellular Carcinoma - Zhao, Mengyao; Li, Benhao; Wu, Yifan; He, Haisheng; Zhu, Xinyan; Zhang, Hongxin; Dou, Chaoran; Feng, Lishuai; Fan, Yong; Zhang, Fan (Advanced materials (Weinheim), 2020)
Deep tissue imaging in the second near‐infrared (NIR‐II) window holds great promise for widespread fundamental research. However, inhomogeneous signal attenuation due to tissue absorption and scattering hampers its application for accurate in vivo biosensing. Here, lifetime‐based in situ hepatocellular carcinoma (HCC) detection in NIR‐II region is presented using a tumor‐microenvironment (peroxynitrite, ONOO−)‐responsive lanthanide–cyanine Förster resonance energy transfer (FRET) nanosensor. A specially designed ONOO−‐responsive NIR‐II dye, MY‐1057, is synthesized as the FRET acceptor. Robust lifetime sensing is demonstrated to be independent of tissue penetration depth. Tumor lesions are accurately distinguished from normal tissue due to the recovery lifetime. Magnetic resonance imaging and liver dissection results illustrate the reliability of lifetime‐based detection in single and multiple HCC models. Moreover, the ONOO− amount can be calculated according to the standard curve. A tumor‐microenvironment‐responsive lanthanide–cyanine Förster resonance energy transfer nanosensor is designed for lifetime‐based hepatocellular carcinoma in situ detection in the second near‐infrared window (1000–1700 nm). Given lifetime measurement is immune to a constant background from ambient light, augmented reality can be integrated to enable a wide range of preclinical biomedical applications.